Improving the anti-keloid outcomes through liposomes loading paclitaxel–cholesterol complexes - Wang MJ (Dove Medical Press, 2019)
Mengjiao Wang,1 Liqing Chen,2 Wei Huang,2 Mingji Jin,2 Qiming Wang,2 Zhonggao Gao,2 Zhehu Jin1 1Klebs Research Center, Department of Dermatology, Yanbian University Hospital, Yanji 133000, China; 2State Key Laboratory of Bioactive Substance and Function of Natural Medicines, Institute of Materia Medica, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100050, China Background: Keloids represent benign fibroproliferative tumors which result from elevated expression of inflammation. Paclitaxel (PTX) was an effective chemotherapeutic agent and has been reported to have anti-fibrotic effects, but the strong hydrophobicity brings a challenge for its clinical application. Purpose: The objective of this study was to improve the water solubility of PTX and investigate its anti-keloid effects. Methods: We prepared a PTX-cholesterol-loaded liposomes (PTXL) by thin film evaporation fashion and characterized their physicochemical properties. We also investigated the effects of PTX on proliferation, invasion and fibrosis of keloid fibroblasts in vitro and in vivo. Results: The prepared PTXL have a spherical appearance, a particle size of 101.43 nm and a zeta potential of -41.63 mV. PTXL possessed a high drug entrapment efficiency of 95.63% and exhibited a good stability within 30 days. The drugs in PTXL were released in a slow and sustained mode. The PTXL could be effectively uptaken into human keloids fibroblast (HKFs) in a time-dependent manner. In vitro, PTXL showed better ability on inhibiting cell proliferation, migration and invasion, and effectively on promoting apoptosis and arresting cell cycle in G2/M phase compared to PTX. Meanwhile, in vivo studies indicated that the PTXL had better performance on inhibiting the keloids growth compared to the PTX in keloid-bearing BALB/c nude mice model. Finally, we found PTX treatment suppressed the production of tumor necrosis factor alpah (TNF-α), interleukin 6 (IL-6) and transforming growth factor beta (TGF-β) and inhibited the expression of alpha smooth muscle actin (β-SMA) and collagen I in HKFs. The activation of protein kinase B (AKT)/glycogen synthase kinase 3 beta (GSK3β) signaling pathway also blocked by PTX in cultured HKFs and keloid tissues. LY294002, a PI3K (phosphatidylinositol 3-kinase)/AKT inhibitor, also suppressed the expression of TNF-α, IL-6 and TGF-β, and simultaneously, reduced the production of α-SMA and collagen I in HKFs. The inhibition of AKT/GSK3β signaling pathway contribute to inhibit the generation of fibrogenic cytokines by PTXL on ameliorating fibrosis progress in keloids. Conclusion: Our results suggested that the developed PTXL would become a promising therapeutic agent in the field of anti-keloid therapy. Keywords: keloids, paclitaxel, liposomes, AKT, GSK3β, fibrosis